2002
DOI: 10.1080/00207450290026166
|View full text |Cite
|
Sign up to set email alerts
|

Xy99-5038 Promotes Long-Term Survival of Cultured Retinal Neurons

Abstract: We have previously reported that XY99-5038, a preparation from a specific formula of Traditional Chinese Medicine, could effectively inhibit hydrogen peroxide-induced retinal cell death. In the present study, we investigated the possibility of XY99-5038 to prolong neuronal survival in a long-term retinal neuronal culture. Basic fibroblast survival factor (bFGF), a potent neurotrophic factor, was employed as comparable agent. Retinas of 0-2 days old Sprague-Dawley rats were isolated and dissociated. The cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Long-term clinical observations and ongoing studies have shown that patients with cancer and other medical conditions received significant beneficial effects from exposure to External Qi of Yan Xin Qigong (YXQ-EQ) without noticeable side effects [8, 9]. A body of substantial experimental studies has been conducted to show the effects of YXQ-EQ at molecular, cellular, and microorganism levels [7, 1014]. Most recently, it was reported that YXQ-EQ exhibited potent cytotoxic effects on BxPC3 pancreatic cancer cells [4], PC3 prostate cancer cells [5] and MDA-MB-231 breast cancer cells [6], respectively, by effectively inhibiting ERK1/2 and/or Akt pathways in these cancer cells, without harming normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term clinical observations and ongoing studies have shown that patients with cancer and other medical conditions received significant beneficial effects from exposure to External Qi of Yan Xin Qigong (YXQ-EQ) without noticeable side effects [8, 9]. A body of substantial experimental studies has been conducted to show the effects of YXQ-EQ at molecular, cellular, and microorganism levels [7, 1014]. Most recently, it was reported that YXQ-EQ exhibited potent cytotoxic effects on BxPC3 pancreatic cancer cells [4], PC3 prostate cancer cells [5] and MDA-MB-231 breast cancer cells [6], respectively, by effectively inhibiting ERK1/2 and/or Akt pathways in these cancer cells, without harming normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…No cytotoxicity to normal cells was observed in these studies with YXQ-EQ. In fact, in vitro studies have found that YXQ-EQ was capable of protecting neurons from oxidative stress induced apoptosis and significantly prolonged survival of neurons [20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…(3) 90 "Protective Effect of XY99-5038 on Hydrogen Peroxide Induced Cell Death in Cultured Retinal Neurons" (Yan et al 2001, 289-299), "XY99-5038 Promotes Long-Term Survival of Cultured Retinal Neurons" ( Yan et al 2002( Yan et al , 1209( Yan et al -1227 " 2014 , 1970).〕…”
mentioning
confidence: 99%